Spatio-temporal changes in plankton in the Ciénaga de Ayapel (Córdoba-Colombia), during the period of lower water level [Cambios espacio-temporales del plancton en la Ciénaga de Ayapel (Córdoba-Colombia), durante la época de menor nivel del agua] (2012)
The spatial and temporal changes of phytoplankton and zooplankton assemblages were evaluated during the period of low water level in the swamp Ciénaga de Ayapel. During seven continuous days, integrated water samples were taken throughout the water column along six sampling stations located north-south across the longitudinal axis of the swamp. During the study period, the swamp acted as a soft, alkaline water system, strongly mixed, with reduced depth and transparency, with noticeable differences in the spatial conditions, and witha high temporal homogeneity of the physical, chemical and biological variables. Both phytoplankton and zooplankton assemblages showed spatial differences and a high temporal homogeneity. Cyanobacteria represented 70% of the total density of phytoplankton, mainly Cylindropermopsis raciborskii and Planktolyngbya limnetica. Zooplankton was represented by the immature stages of copepods (mainly naiplii) and rotifers of the genus Brachionus.